THE PHENOMENON OF EMPTY BOXES IN THE 2024 REGIONAL ELECTIONS IN PAKPAK BHARAT DISTRICT: ANALYSIS OF ISLAMIC POLITICAL THOUGHT - Lolo Ate Karina Berutu; Zulkarnain (RADJA PUBLIKA, 2026)
One of the phenomena that has drawn attention in the practice of local democracy in Indonesia is the emergence of a single candidate pair competing against the “empty box” option in regional head elections. This situation reflects issues in democratic competition, the dominance of political party coalitions, and weaknesses in the political recruitment process. The election of the Regent and Deputy Regent of Pakpak Bharat in 2024 serves as a concrete example, where only one candidate pair contested against the empty box. This study aims to analyze the empty box phenomenon in the 2024 Regional Head Election of Pakpak Bharat and to examine it from the perspective of Islamic political thought. The research employs a qualitative approach with a descriptive-analytical method. Data were collected through interviews with informants from the General Election Commission (KPU), the Election Supervisory Agency (Bawaslu), religious leaders, community members, and political parties in Pakpak Bharat, supported by documentation studies of legislation, academic journals, and media reports. The findings reveal that the empty box phenomenon in Pakpak Bharat was influenced by the dominance of a coalition of eleven political parties that supported a single candidate pair, resulting in an unbalanced electoral competition. The absence of independent candidates or alternative pairs meeting the nomination requirements left the public with only two choices: supporting the sole candidate pair or voting for the empty box. From the perspective of Islamic political thought, this condition indicates the suboptimal implementation of the principle of shura (consultation) in recruitment and raises issues of democratic legitimacy due to the limited political leadership options available to society. The study concludes that the empty box phenomenon is a consequence of elite dominance and political party coalitions in the nomination process, which negatively impacts the quality of local democracy. Therefore, it is necessary to strengthen more inclusive political recruitment mechanisms and to implement Islamic political values that uphold the principles of shura, justice, trustworthiness (amanah), and public participation in the democratic process.